2023
DOI: 10.1186/s40537-023-00751-2
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of Big Data in neuroscience and neurology

Abstract: Neurological diseases are on the rise worldwide, leading to increased healthcare costs and diminished quality of life in patients. In recent years, Big Data has started to transform the fields of Neuroscience and Neurology. Scientists and clinicians are collaborating in global alliances, combining diverse datasets on a massive scale, and solving complex computational problems that demand the utilization of increasingly powerful computational resources. This Big Data revolution is opening new avenues for develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
3

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 271 publications
0
11
0
3
Order By: Relevance
“…The publicly available UK Biobank dataset [21], for instance, collects hundreds of thousands of genetic and behavioral data as well as tens of thousands of multimodal brain imaging. In the current big data era [20] (see review for public neuroimaging datasets [19,100]), how to fully utilize multimodal information is also a significant challenge. Multimodal analysis techniques based on deep learning have made great progress [101], in which techniques such as reinforcement learning [102] and multimodal generalized foundation models [103,104] can be combined with brain parcellations to achieve better performance via the fusion of complementation information across multimodal.…”
Section: Hierarchy Dynamic and Multimodalitymentioning
confidence: 99%
See 1 more Smart Citation
“…The publicly available UK Biobank dataset [21], for instance, collects hundreds of thousands of genetic and behavioral data as well as tens of thousands of multimodal brain imaging. In the current big data era [20] (see review for public neuroimaging datasets [19,100]), how to fully utilize multimodal information is also a significant challenge. Multimodal analysis techniques based on deep learning have made great progress [101], in which techniques such as reinforcement learning [102] and multimodal generalized foundation models [103,104] can be combined with brain parcellations to achieve better performance via the fusion of complementation information across multimodal.…”
Section: Hierarchy Dynamic and Multimodalitymentioning
confidence: 99%
“…With the progressive development of neuroimaging technology and large-scale databases, parcellation research has come into a 'big data' era [18][19][20]. For instance, UK Biobank [21], the largest brain imaging database, currently has more than 40 000 fMRI samples, and each sample contains more than 100 000 voxels and 490 time points.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Li Y. et al demonstrated that CT imaging features and markers of small vessel disease are predictive of the presence of >10 cerebral microbleeds on MRI. More research is needed before Big Data analysis such as artificial intelligence and machine learning can be more ubiquitously applied to clinical care ( 2 6 ).…”
mentioning
confidence: 99%
“…Big Data analytics is a rapidly evolving field and there are important considerations and pauses that should be factored into data interpretation and application. It is important to be aware of biases that may be present in datasets as a result of patient recruitment ( 1 6 ). Even within large datasets, there may be unknown missing confounders.…”
mentioning
confidence: 99%
See 1 more Smart Citation